Implementasi Arsitektur Jaringan Komputer di Laboratorium Komputer Unsika - Ade Andri Hendriadi; Azhari Ali Ridha; Arip Solehudin (Universitas Singaperbangsa Karawang)
Abstract - Internet access is very important to looking for and sending information. Internet usefull for knowing new information especially about technology in crease but also can be down of studies quality. At practice goes on so the student in permit for un access internet because it will be concentrate of student who has practice (except internet practice). Master data who was more than 700 user not be stabelize so will be need server ClearOS as master data and mikrotik router for user hotspot with using topology new network. The method who has used for this research using mono polating method with forward enginering method with research step following to Network Development Life Cycle (NDLC). Result of design application and architecture implementation network of computer laboratory UNSIKA are with apply bandwith management using ClearOS can be border on internet access while practice in computer laboratory UNSIKA, except that who was used internet facility. With appliying mikrotik router as user management hotspot beetween giving upload/download with maximal, user name and password can be border on internet access by hotspot in computer laboratory UNSIKA. With using router mikrotik and server ClearOS can be manage and knowing bandwith effect for network access local and internet, so can be based of learning process about network management, with applying ClearOS as master data in computer laboratory UNSIKA can be solve of manage more then 700 user.Kata Kunci: Network Architecture, Network Topology, Server ClearOS, Mikrotik Router, WEBHTB, and Bandwidth Management.